PENGARUH KARAKTERISTIK, KOMPLEKSITAS DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH DI PROVINSI GORONTALO - Hiola, Yustina; Harun, Ervina (JSAP : Journal Syariah and Accounting Public, 2021)
The research was conducted at the Financial Audit Agency of the Republic of Indonesia, Representative of the Province of Gorontalo. The purpose of this study is to find out how the Influence of Characteristics, Complexity and Audit Findings on the Level of Disclosure of Local Government Financial Statements in Gorontalo Province. This study uses multiple linear regression where the dependent variable is the level of disclosure of local government financial statements and the independent variables are the size of the local government, regional independence, transfer income, number of regional apparatus organizations, legislative size and audit findings. From the results of research conducted partially the size of the local government has a significant effect on the level of disclosure of local government financial statements in Gorontalo Province in 2018-2020, regional independence has a significant effect on the level of Disclosure of local government financial statements in Gorontalo Province in 2018-2020, transfer income has no effect significantly to the level of disclosure of local government financial statements in Gorontalo Province in 2018-2020, the number of regional apparatus organizations did not significantly affect the level of disclosure of local government financial statements in Gorontalo Province in 2018-2020, the size of the legislature had a significant effect on the level of disclosure of local government financial statements in Gorontalo Province in 2018-2020 and audit findings have a significant effect on the level of disclosure of local government financial statements in Gorontalo Province in 2018-2020